2016
DOI: 10.1038/npjpcrm.2016.73
|View full text |Cite
|
Sign up to set email alerts
|

Change in health status in COPD: a seven-year follow-up cohort study

Abstract: Health status is a prognostic factor included in the assessment of chronic obstructive pulmonary disease (COPD). The aim of our study was to examine the associations of clinical factors with change in health status over a 7-year follow-up period. In 2005, 970 randomly selected primary and secondary care patients with a COPD diagnosis completed questionnaires including the Clinical COPD Questionnaire (CCQ); and in 2012, 413 completed the CCQ questionnaire again. Linear regression used difference in mean total C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
(45 reference statements)
2
11
1
Order By: Relevance
“…Either weak or no correlations among symptom domain, mental domain, and post-bronchodilator FEV1% predicted were observed in previous studies [30][31][32]. Our study also revealed that underweight was independently associated with higher score on the total CCQ and mental domain, which was consistent with the results of Sundh et al [8,11]; in addition, BMI < 25 kg/m 2 was significantly associated with lower health-related quality of life assessed by CCQ in a prospective study with 7 years of follow-up [33].…”
Section: Discussionsupporting
confidence: 92%
“…Either weak or no correlations among symptom domain, mental domain, and post-bronchodilator FEV1% predicted were observed in previous studies [30][31][32]. Our study also revealed that underweight was independently associated with higher score on the total CCQ and mental domain, which was consistent with the results of Sundh et al [8,11]; in addition, BMI < 25 kg/m 2 was significantly associated with lower health-related quality of life assessed by CCQ in a prospective study with 7 years of follow-up [33].…”
Section: Discussionsupporting
confidence: 92%
“…Younger patients experienced significantly worse health status and dyspnea compared with elderly [5,73]. However, older age has also been associated with worse health status [5,14]. In the present study, MCID estimates were larger for improvement and smaller for deterioration in elderly, although not all significant.…”
Section: Gender Age and Comorbiditiesmentioning
confidence: 46%
“…Many factors may impact health status in COPD, including the number and severity of exacerbations [8e10]; the disease severity defined according to the Global initiative for Obstructive Lung Disease (GOLD) spirometry classification [5,9e12]; the patient's gender and age [5,8e10,13e15]; and the amount of comorbidities [12]. Moreover, the baseline score may also be predictive of (worsening) health status [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…When adjusting for spirometric stage of COPD, deteriorated HRQoL was found to be predicted by increasing dyspnea, depression/anxiety, an increasing number of exacerbations, and decreased exercise capacity [6]. Other signs of deteriorating COPD disease are disabling breathlessness [7] and low body mass index [8]. …”
Section: Introductionmentioning
confidence: 99%